The Nightmare affair - Arnett, Mindee (Tor Teen, 2014)
Being the only Nightmare at Arkwell Academy, a boarding school for "magickind," sixteen-year-old Destiny Everhart feeds on the dreams of others, working with a handsome human student to find a killer.